AB0037 CD4+CD25-GITR+regulatory T cells are expanded in the blood, display suppressive function and are inversely correlated with disease activity in patients with primary Sjögren's syndrome. (23rd January 2014) - Alunno, A.; Nocentini, G.; Bartoloni, E.; Petrillo, M.G.; Bistoni, O.; Ronchetti, S.; Santoboni, G.; Valentini, V.; Riccardi, C.; Gerli, R.
Abstract : Background: In the last years, several molecules have been suggested as marker of human regulatory T cells (Treg), including GITR (glucocorticoid-induced TNFR-related gene), a specific marker of murine Treg cells. We recently provided evidence for a CD4 + CD25 - FoxP3 + T-cell population that displays high surface levels of GITR and exerts in vitro suppressive activity in healthy subjects. Objectives: Aim of the present study was to investigate phenotype and function of circulating CD4 + CD25 - GITR + cells in patients with primary Sjögren's syndrome (pSS). Methods: Thirty pSS patients and 30 normal controls (NC) were enrolled. Peripheral blood mononuclear cells (PBMCs) were separated by magnetic sorting and phenotypic characterization was performed by both flow cytometry and real-time PCR (FoxP3, CTLA-4, TGF-β). Functional assays were performed, by co-culturing magnetic sortedCFSE-stained effector T cells with the CD4 + CD25 - GITR + cell subset obtained from SS patients and HD. Results: In pSS patients, circulating CD4 + CD25 - GITR + cells were expanded, whereas CD4 + CD25 high GITR + Treg cells were reduced. CD4 + CD25 - GITR + cells expressed Treg markers and displayed suppressive activity in vitro. In particular, similarly to in HD CD25-G+ cells, SS CD25 - G + T cells inhibit autologous effector T cells proliferation, but to a lesser extent. We observed an inverse correlation between the percentage of circulating CD4 + CD25 - GITR + cells and the EULAR Sjögren's syndrome disease activity index (ESSDAI) (p<0.05). Immunofluorescence studies of minor salivary glands in pSS to identify CD4 + CD25 - GITR + cells are currently ongoing. Conclusions: pSS patients display an expansion of CD4 + CD25 - GITR + Treg subset which is functionally suppressive. Moreover, the CD4 + CD25 - GITR + Treg subset is lower in active pSS as compared to inactive pSS, leading to the hypothesis that a strong inflammatory response, reflecting higher disease activity, could determine an imbalance of this cell subset. References: Bianchini R et al. Eur J Immunol 2011;41:2269 Gerli R et al. Autoimmunity Rev 2009;8:426 Disclosure of Interest: None Declared